2020
DOI: 10.46497/archrheumatol.2020.7783
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcitonin Gene-Related Peptide and Receptor Protein Levels in Patients With Fibromyalgia Syndrome: A Cross-Sectional Study

Abstract: Objectives This study aims to compare the serum calcitonin gene-related peptide (CGRP) and CGRP receptor protein levels between patients with fibromyalgia syndrome (FM) and healthy control subjects. Patients and methods The study included 88 patients (7 males, 81 females; mean age 44.5±9.1 years; range, 20 to 72 years) newly-diagnosed with FM according to the 2010 American College of Rheumatology criteria and 88 healthy volunteers (6 males, 82 females; mean age 43.0±6.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…FMRP puncta colocalized with CGRP+ loci in the spinal branches of primary nociceptors in female but not male donor spinal cord. Maladaptive changes in CGRP signaling are emerging as a feature of many chronic pain phenotypes specifically in females (Avona et al, 2019, 2021; Casale et al, 2021; Iyengar et al, 2017; KORUCU et al, 2020; Paige et al, 2022; Siracusa et al, 2021; Sluka & Clauw, 2016; Tavares-Ferreira, Ray, et al, 2022). In female rodents, spinal CGRP signaling plays an important role in multiple chronic pain models by regulating excitatory/inhibitory balance in intrinsic spinal cord neurons (Paige et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMRP puncta colocalized with CGRP+ loci in the spinal branches of primary nociceptors in female but not male donor spinal cord. Maladaptive changes in CGRP signaling are emerging as a feature of many chronic pain phenotypes specifically in females (Avona et al, 2019, 2021; Casale et al, 2021; Iyengar et al, 2017; KORUCU et al, 2020; Paige et al, 2022; Siracusa et al, 2021; Sluka & Clauw, 2016; Tavares-Ferreira, Ray, et al, 2022). In female rodents, spinal CGRP signaling plays an important role in multiple chronic pain models by regulating excitatory/inhibitory balance in intrinsic spinal cord neurons (Paige et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…FMRP puncta colocalized with CGRP+ loci in the spinal branches of primary nociceptors in female but not male donor spinal cord. Maladaptive changes in CGRP signaling are emerging as a feature of many chronic pain phenotypes specifically in females (Avona et al, 2019(Avona et al, , 2021Casale et al, 2021;Iyengar et al, 2017;KORUCU et al, 2020;Paige et al, 2022;Siracusa et al, 2021;Sluka & Clauw, 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…Some chemokines, cytokines and neuromodulators are known to function during postsynaptic and presynaptic processing of a peripheral nociceptive stimulus in the CNS (2). It has been suggested that hyperalgesia and allodynia develop due to increases or inhibition loss in membrane excitability and synaptic activity through reductions or increases in the inhibitor and excitatory neurotransmitters (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Fibromiyalji Sendromu (FMS) yaygın ağrı ile karakterize kronik bir kas iskelet sistemi hastalığıdır (1). FMS'nin etyopatogenezi henüz net olarak bilinmemekle birlikte genetik, çevresel ve immünolojik faktörlerin, periferik ve santral mekanizmaların rol oynadığı düşünülmektedir (2,3). Daha önce yapılan bazı klinik çalışmalarda hipotalamik-pituiter-adrenal (HPA) aksta meydana gelen bir bozukluğun FMS patogenezinde rol oynayabileceği bildirilmiştir (4,5).…”
Section: Introductionunclassified